1989
DOI: 10.1177/109634808901300313
|View full text |Cite
|
Sign up to set email alerts
|

Employee Job Satisfaction Determinants Within a National Restaurant Company

Abstract: Nonmanagement employee turnover has long been a major concern to acade micians and business professionals. The general purpose of this study is to develop a more complete understanding of the employee turnover process for full-time and part-time employees by identifying job satisfaction determinants. The identification of specific job satisfaction determinants can be used to develop organizational strategies to control restaurant employee turnover and increase employee retention rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The context 01 a job can be defined as the immediate work environment, which includes satisfaction with employees and supervisory experiences, receipt of recognition and feedback, work-unit size, and satisfaction with peer group interactions (Porter & Steers, 1973;Sneed, 1988;Tas, Spalding, & Getty, 1989). Prior research reported that variables that influence job context also are fairly consistent predictors of employee turnover (Dienhart, 1991).…”
Section: The Studymentioning
confidence: 97%
“…The context 01 a job can be defined as the immediate work environment, which includes satisfaction with employees and supervisory experiences, receipt of recognition and feedback, work-unit size, and satisfaction with peer group interactions (Porter & Steers, 1973;Sneed, 1988;Tas, Spalding, & Getty, 1989). Prior research reported that variables that influence job context also are fairly consistent predictors of employee turnover (Dienhart, 1991).…”
Section: The Studymentioning
confidence: 97%
“…One paper presented a study that examined the measurement items of job satisfaction (Khalilzadeh et al, 2013). Three papers discussed the difference between job satisfaction of different people, such as full-time and part-time employees (Tas et al, 1989) and first employment sector and current employment sector (Kang and Gould, 2002). The job satisfaction of hotel workers in different countries also varied (Fisher et al, 2010).…”
Section: Othersmentioning
confidence: 99%
“…The Job Descriptive Index was used by Tas, Spalding, and Getty (1989) to examine the employee turnover process for full-time and part-time employees by identifying job satisfaction determinants. They found no statistically significant differences between part-time and full-time employees on their level of satisfaction with present pay, supervision, coworkers, and job in general.…”
Section: Job Satisfaction Research In the Hospitality Industrymentioning
confidence: 99%